Extrinsic polarization-controlled optical anisotropy in plasmon-black phosphorus coupled system. (14th May 2018) - Liu, Zizhuo; Wells, Spencer A; Butun, Serkan; Palacios, Edgar; Hersam, Mark C; Aydin, Koray
Abstract: Two-dimensional black phosphorus (BP) has drawn extensive research interest due to its promising anisotropic photonic and electronic properties. Here, we study anisotropic optical absorption and photoresponse of exfoliated BP flakes at visible frequencies. We enhance this intrinsic optical anisotropy in BP flakes by coupling plasmonic rectangular nanopatch arrays that support localized surface plasmon resonances. In particular, by combining extrinsic anisotropic plasmonic nanostructures lithographically aligned with intrinsically anisotropic BP flakes, we demonstrate for the first time a combined anisotropic plasmonic-semiconductor coupling that provides significant control over the polarization-dependent optical properties of the plasmon-BP hybrid material system, enhancing polarization-sensitive responses to a larger degree. This hybrid material system not only unveils the plasmon-enhanced mechanisms in BP, but also provides novel controllable functionalities in optoelectronic device applications involving polarization-sensitive optical and electrical responses.